A comparative study on scanned fingerprint after applying lubricants and without scanned fingerprint on porous surface; (white paper). (2022) - Aseri, Vinay; Nagar, Varad; Godara, Vanisha; Pandit, Pritam P.; Chopade, Rushikesh L.; Verma, Rohit; Sharma, Anuj; Parihar, Kapil; Kant Awasthi, Kumud; Singh, Apoorva
Abstract: Specialists have concocted various ways for recognizing inert fingerprints on crime locations. The powder method is an exceptionally basic way of developing fingerprints. Fingerprinting is one of those fields, the modernized scanner displaced ordinary procedures for taking fingerprints. In daily life, individuals regularly apply oils, salves, hand sanitizers, at times on their hands. These restoratives and day by day use items influence the computerized recording of fingerprints, along these lines making it hard for measurable specialists to recognize the genuine wrongdoer in numerous cases. The study was to actually look at the impact of oils, creams, hand sanitizers, and ghee on the fingerprints. For this research, various lubricants were applied on the fingerprint of plain white paper. Lubricants were applied on fingers and were then scanned. 39 fingerprints were taken. These fingerprints were then recorded with the assistance of 20 secugen hamsters. The assessment and examination of finger impression were done. The presence of everyday use items influenced the quality of fingerprints. Different items caused various impacts depending on their properties. Engineered ghee, hand sanitizer, slick balm, and greasy oil ruined the fingerprint quality, resulting in massive differences in the finger impression photographs. Non-slick cream and alcohol-free hand sanitizer had less effect, whereas oil and regular ghee had no influence on the notion of fingerprints. The combination of lubricants added an extra layer to the fingers. This layer caused changes to the fingerprint impressions. As a result, fingerprints should be collected after proper hand washing.